The Savvy Survey #2: Using Surveys in Everyday Extension Programming - Jessica L. Gouldthorpe; Glenn D. Israel (EDIS, 2013)
This second publication in the Savvy Survey Series provides Extension faculty with additional information about using surveys in their everyday Extension programming. The publication suggests how surveys can be used in needs and assets assessments to inform program development, as formative and summative evaluations to support program improvement, and as customer service tools to capture satisfaction within programming efforts. This publication also introduces the concept of using logic models to guide questionnaire development, while also discussing general data types (demographics, factual information, attitudes and opinions, behaviors and events). This 5-page fact sheet was written by Glenn D. Israel and Jessica L. Gouldthorpe, and published by the UF Department of Agricultural Education and Communication, October 2013. http://edis.ifas.ufl.edu/pd062